Viie aasta elulemus pärast plaanilist aordi aneurüsmi ravi avatud ja endovaskulaarsel meetodil - Lieberg, Jüri; Kadatski, Karl G.; Kals, Mart; Paapstel, Kaido; Kals, Jaak (Eesti Arst, 2023)
Eesti Arst 2023; 102(6–7):358